Toward novel antiparasitic formulations: Complexes of Albendazole desmotropes and β-cyclodextrin. (15th May 2017) - Chattah, Ana K.; Pfund, Laura Y.; Zoppi, Ariana; Longhi, Marcela R.; Garnero, Claudia
Highlights: Complexes of two solid forms of albendazole with β-cyclodextrin were obtained. Albendazole:β-cycldoextrin solid complexes were characterized. Results indicate that the complexes are promising matrices for drug delivery. Abstract: Novel complexes of two different solid forms of Albendazol and β-cyclodextrin were investigated in an attempt to obtain promising candidates for the preparation of alternative matrices used in pharmaceutical oral formulations. The interaction between each form of Albendazol and β-cyclodextrin was studied in solution and solid state, in order to investigate their effect on the solubility and dissolution rate of Albendazol solid forms. The solid supramolecular systems were characterized using a variety of techniques including natural-abundance 13 C cross-polarization magic-angle-spinning nuclear magnetic resonance, powder X-ray diffraction, Fourier transform-infrared spectroscopy and scanning electron microscopy. The results obtained showed the highest increment of solubility and dissolution rate, in simulated gastric fluid, for the Albendazole II:β-cyclodextrin systems. Thus, these new complexes constitute an interesting alternative for improving the oral bioavailability of Albendazol.